Cross-Talk between Gut Microbiota and Heart via the Routes of Metabolite and Immunity - Jin Bu; Zhaohui Wang (Gastroenterology Research and Practice)
Considering the prevalence of cardiovascular disease (CVD), significant interest has been focused on the gut microbiota-heart interaction because the gut microbiota has been recognized as a barometer of human health. Dysbiosis, characterized by changes in the gut microbiota in CVD, has been reported in cardiovascular pathologies, such as atherosclerosis, hypertension, and heart failure. Conversely, gut microbiota-derived metabolites, such as trimethylamine/trimethylamine N-oxide (TMA/TMAO), can impact host physiology. Further, bacterial dysbiosis can disturb gut immunity, which increases the risk of acute arterial events. Moreover, studies of germ-free mice have provided evidence that microbiota diversity and the presence of a specific microbe in the gut can affect immune cells in hosts. Therefore, the changes in the composition of the gut microbiota can affect host metabolism and immunity. Importantly, these effects are not only confined to the gut but also spreaded to distal organs. The purpose of the current review is to highlight the complex interplay between the microbiota and CVD via TMAO and different immune cells and discuss the roles of probiotics and nutrition interventions in modulating the intestinal microbiota as novel therapeutic targets of CVD.